Breaking ground: transformative partnerships for inclusive bean breeding in Zimbabwe - Nchanji, Eileen Bogweh; Chisorochengwe, Nyarai; Tsekenedza, Shylet; Gutsa, Freeman; Musyoka, James Ndambuki; Lutomia, Cosmas Kweyu (Frontiers in Sustainable Food Systems, 2024)
Common bean is often considered a woman’s crop because of roles they play from production to marketing. However, breeding programs often focus on farmers without adequate attention to the interconnectedness between gender and other socioeconomic variables and how they influence varietal and trait preferences of other value chain actors. This study analysed gendered differences in objectives of bean production and trade, implications of socioeconomic conditions on bean production and marketing, and the role of partnerships in closing gender gaps in the bean value chain in Zimbabwe. Results obtained from analysis of survey data collected from 131 farmers and 18 trades revealed beans as a dual-purpose crop for men and women farmers and traders. Varietal and trait preferences were the same for both men and women farmers and traders but were prioritized differently. While women farmers prioritized cooking time, men prioritized biofortification and market traits. Whereas men traders equally preferred price, colour, and appearance, women traders prioritized price over colour and appearance. Poverty and marital statuses of respondents influenced the number of varieties preferred by men and women farmers. We found that the effectiveness of partnerships in closing gender gaps in marketing are variety specific. While having partners nearly closed the gender gaps in the marketing of the NUA45 variety, such partnerships did not have the same effect on closing gender gaps in the marketing of Cherry, Gloria, and other varieties. The results show that considering socioeconomic characteristics of actors and partnerships can reduce gender disparities in the bean value chain. Therefore, breeding programmes should recognise the interconnectedness between socio-economic variables and gender when developing breeding products.